Phosphorus–nitrogen compounds. Part 37. Syntheses and structural characterizations, biological activities of mono and bis(4-fluorobenzyl)spirocyclotetraphosphazenes. (7th June 2017) - Elmas, Gamze; Okumuş, Aytuğ; Sevinç, Pelin; Kılıç, Zeynel; Açık, Leyla; Atalan, Mustafa; Türk, Mustafa; Deniz, Gökberk; Hökelek, Tuncer
Abstract : The syntheses, spectroscopic and crystallographic properties, in vitro cytotoxic and antimicrobial activities of the cyclotetraphosphazenes were investigated. Abstract : The Cl substitution reactions of octachlorocyclotetraphosphazene, N4 P4 Cl8, with one equimolar amount of (4-fluorobenzyl)diamines (1–3 ) affords mono(4-fluorobenzyl)spirocyclotetraphosphazenes (4–6 ) as minor products. However, the reactions of N4 P4 Cl8 with two equimolar amounts of (4-fluorobenzyl)diamines (1–3 ) leads to the formation of mono (4–6 ), 2- trans -6-bis (7–9, as major products) and 2- cis -6-bis (4-fluorobenzyl)spirocyclotetraphosphazenes (10–12 ). The 2- cis -6-bis compounds (10 and12 ) were separated and purified using column chromatography as minor products, whereas compound11 could not be isolated. The mono-spiro (4–6 ) and 2- trans -6-bis-spiro (7–9 ) cyclotetraphosphazenes were reacted with excess pyrrolidine in THF to afford the fully substituted hexapyrrolidino (4a-6a ) and tetrapyrrolidino (7a-9a ) products in high yield. Compound9 was also reacted with piperidine, morpholine and 1, 4-dioxa-8-azaspiro[4, 5]decane (DASD) to obtain the tetraamino products (9b, 9c and9d ), respectively, due to its very high yield. The elemental analyses, mass spectra (ESI-MS), Fourier transform infrared (FTIR) spectra, and 1 H, 13 C{ 1 H}, and 31 P{ 1 H} NMR data of the cyclotetraphosphazenes were in agreement with the suggested structures. The molecular structures of7, 9 and12 were established by X-ray crystallography. The antibacterial activities of the compounds against G(+) and G(−) bacteria and their antifungal activities against yeast strains were scrutinized. The results indicated that4a and5a were the most active compounds, especially to yeast strains. In addition, it was found that the most active compound toward DNA was8 . The cytotoxic activities of the cyclotetraphosphazenes against L929 fibroblast and MCF-7 breast cancer cell lines were elucidated. Compound8a exhibited the most toxic effects against both types of cells.